Мотив адюльтера в романе Анатолия Мариенгофа Циники: слом или продолжение традиций русского словесно-культурного процесса? - Shestakova, Eleonora (Studia Rossica Posnaniensia, 2024)
Cynics as the poetics and worldview of imagism suggests, gives the impression of a kind of novel-rebellion against Russian literary culture that has developed since the era of Pushkin. This is despite the fact that Mariengof at the end of the 1920s, when predictably dominated by social-political issues, creates a novel about a love story, seemingly quite traditional for Russian literature. This novel is not only about a love story, however, but also about adultery, proposed almost as a norm in married life. This violates and partly as it were destroys the traditions developed by the Russian literary process in the sphere of motives. Love stories and adulteries are inscribed in the motif, gradually gaining strength, of marital unfaithfulness which increases the independent poetics in Russian literature. According to literary scholars, adultery has its origins in the prose of Pushkin, and Lermontov, and it is further developed by Leo Tolstoy. However, researchers have not paid enough attention to the genres of the romantic, secular novella of the 1820s–1840s, with Turgenev’s works as another line of adultery, largely autonomous, experiencing the natural influence of the European medieval tradition. From this angle, the motif of adultery in Cynics has an “external” dimension, correlating with historical time, a catastrophic social-political situation, and internal literary history, as Veselovsky designated it. This naturally and inextricably connects the novel with the thickness of national and Western European literary meanings, images, types of heroes, and conflicts.